HEALTH PLAN OF MUNICIPALITIES OF THE ONE REGIONAL HEALTH OF PARANA - Gleyce Mara Freitas; Tatiane Baratieri; Calíope Pilger (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927716 Objective: to analyse the knowledge of health Secretaries, about the preparation of the Municipal Health Plan (MHP) of municipalities that comprise the 5th Health Regional of Paraná, as its your process, difficulties and relevance to municipal management. Methods: a quantitative study, exploratory. The datas were collected with eight municipal health Secretariats, through self-administered semi-structured questionnaire, in October and November 2011. Results: the researcher claimed to have the MHP, but are unaware of the frequency of the preparation; 75% contributed to the development; 85,7% never have guidance/ capacity building to elaborate the MHP; 50% reported that the plan was prepared by staff from the municipal health Secretary. Conclusion: the elaboration of MHP of the 5° health regional municipalities has limitations, due to this, is necessary to update managers, receive aid from state and federal spheres, plan for and involve of health professionals, seen as, the MHP is an important instrument of municipal management.